Spinal infections in children: a multicentre retrospective study. (April 2018) - Dayer, R.; Alzahrani, M. M.; Saran, N.; Ouellet, J. A.; Journeau, P.; Tabard-Fougère, A.; Martinez-Álvarez, S.; Ceroni, D.
Abstract : Aims: This multicentre, retrospective study aimed to improve our knowledge of primary pyogenic spinal infections in children by analyzing a large consecutive case series. Patients and Methods: The medical records of children with such an infection, treated at four tertiary institutions between 2004 and 2014, were analyzed retrospectively. Epidemiological, clinical, paraclinical, radiological, and microbiological data were evaluated. There were 103 children, of whom 79 (76.7%) were aged between six months and four years. Results: We confirmed a significant male predominance in the incidence of primary pyogenic spinal infections in children (65%). The lumbar spine was the most commonly affected region, and 27 infections (26.2%) occurred at L4/5. The white blood cell count was normal in 61 children (59%), and the CRP level was normal in 43 (42%). Blood cultures were performed in 95 children, and were positive in eight (8%). A total of 20 children underwent culture of biopsy or aspiration material, which was positive in eight (40%). Methicillin-sensitive Staphylococcus aureus (MSSA) and Kingella ( K. ) kingae were the most frequently isolated pathogens. Conclusion: MSSA remains the most frequently isolated pathogen in children with primary pyogenic infection of the spine, but K. kingae should be considered as an important pathogen in children aged between six months and four years. Therefore, an empirical protocol for antibiotic treatment should be used, with consideration being made for the triphasic age distribution and specific bacteriological aetiology. In the near future, the results of polymerase chain reaction assay on throat swabs may allow the indirect identification of K. kingae spondylodiscitis in young children and thus aid early treatment. However, these preliminary results require validation by other prospective multicentre studies. Cite this article: Bone Joint J 2018;100-B:542–8.